The economic consequences of Brexit on free movement of goods, services, people and capital - Nguyen, Kieu Hanh; Křečková Kroupová, Zuzana, 1972-; JACKSON, Ian; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2018)
The aim of my dissertation thesis is to analyze the economic impact of Brexit on four free movements of goods, services, people and capital from perspectives of different literature reviews. I would like to get an appropriate answer to my research question, whether British exit from the European Union will have a negative impact on free movements of goods, services, people and capital in the short and long run. I am fully aware of the fact that the future depends on the decision made by politicians of both parties, especially on future negotiation´s agreements. Both parties will have to decide on alternative further cooperation and taking into account all benefits and detriments of economic consequences. Thus, this thesis is focusing on Brexit impact on four freedoms in connection with the future relationship between the UK and the EU.
Vedoucí práce: Zuzana Křečková Kroupová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: economics of globalisation and european integration [obor dipl. práce]; diplomové práce; master's theses